Proceedings of the First International Volga Region Conference on Economics, Humanities and Sports (FICEHS 2019) 2019
DOI: 10.2991/aebmr.k.200114.024
|View full text |Cite
|
Sign up to set email alerts
|

The Intellectual Capital Role in Market Growth of Companies in Developed and Emerging Markets

Abstract: The modern economy became increasingly dependent on intellectual capital, whose role is steadily growing in comparison with other types of capital. On the one hand it happens due to the objective trend of the world economy innovative development on the eve of the sixth technological mode beginning; on the other hand, to increased competition between companies from different countries in an increasingly globalized world market. The growing importance in the overall system of companies' competitiveness factors i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…However, the study found no evidence that IFRS adoption significantly impacts the level of disclosure of intellectual capital, intangible assets, and knowledge assets [17]. Other studies show that the accounting system used in the modern economy practically ignores the intellectual capital component [38]. Therefore, there is a need for further development of the concept of intellectual capital and harmonization of intellectual capital reporting [16].…”
Section: Standardsmentioning
confidence: 87%
“…However, the study found no evidence that IFRS adoption significantly impacts the level of disclosure of intellectual capital, intangible assets, and knowledge assets [17]. Other studies show that the accounting system used in the modern economy practically ignores the intellectual capital component [38]. Therefore, there is a need for further development of the concept of intellectual capital and harmonization of intellectual capital reporting [16].…”
Section: Standardsmentioning
confidence: 87%
“…Moreover, Yang et al (2017) found a knowledge-based resource to be transferrable enhances adaptability in changing business environments. The financial and market growth are augmented by intellectual capital in the studies of Sardo and Serrasqueiro (2018) and Dzhioev and Gurieva (2020).…”
Section: Literature Reviewmentioning
confidence: 99%